Facioscapulohumeral dystrophy: activating an early embryonic transcriptional program in human skeletal muscle. (28th April 2018) - Campbell, Amy E; Belleville, Andrea E; Resnick, Rebecca; Shadle, Sean C; Tapscott, Stephen J
Abstract: Facioscapulohumeral dystrophy (FSHD) is the third most prevalent muscular dystrophy. A progressive disease, it presents clinically as weakness and wasting of the face, shoulder and upper arm muscles, with later involvement of the trunk and lower extremities. FSHD develops through complex genetic and epigenetic events that converge on a common mechanism of toxicity with mis-expression of the transcription factor double homeobox 4 (DUX4). There is currently no treatment available for FSHD. However, the consensus that ectopic DUX4 expression in skeletal muscle is the root cause of FSHD pathophysiology has allowed research efforts to turn toward cultivating a deeper understanding of DUX4 biology and the pathways that underlie FSHD muscle pathology, and to translational studies aimed at developing targeted therapeutics using ever more sophisticated cell and animal-based models of FSHD. This review summarizes recent advances in our understanding of FSHD, including the regulation and activity of DUX4 in its normal developmental roles as well as its pathological contexts. We highlight how these advances raise new questions and challenges for the field as it moves into the next decade of FSHD research.